1980
DOI: 10.1042/bj1890001
|View full text |Cite
|
Sign up to set email alerts
|

The quarternary structure of an unusual high-molecular-weight intracellular haemoglobin from the bivalve mollusc Barbatia reeveana

Abstract: The arcid clam Barbatia reeveana contains an intracellular haemoglobin with an unusual structure. First, compared with other intracellular haemoglobins, it is extremely large, with a mol.wt. of 430000 and an s20,w of 13.6S. A minor component (mol.wt. = 220000; s2O,w = 9.7S) is also present as a probable dissociation product of the major component. Secondly, this haemoglobin has an unusual subunit structure. It contains 1 mol of haem per 16000 g of protein, in common with most other haemoglobins. However, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…For example, Jawad et al, (2004), found that the values of Hb, RBC and PCV increased as the fish size increase. Similar result were obtained for Clarias batrachus (Jushi & Tardon, 1977), Tilapia zilli (Ezzat et al, 1973), Cyprinus Carpio, bivalve Barlatia reevena (Grinich & Terwilliger, 1980) and Amphiprous cuchia (Banerjee, 1986). It should be noted that the differences recorded in blood parameters between various sizes according to Paizada et al, (1983), are genetically determined, but Chaudhuri et al, (1986) suggested that the difference might be due to the higher metabolic rate, of the bigger fish compared to smaller ones.…”
Section: Discussionsupporting
confidence: 71%
“…For example, Jawad et al, (2004), found that the values of Hb, RBC and PCV increased as the fish size increase. Similar result were obtained for Clarias batrachus (Jushi & Tardon, 1977), Tilapia zilli (Ezzat et al, 1973), Cyprinus Carpio, bivalve Barlatia reevena (Grinich & Terwilliger, 1980) and Amphiprous cuchia (Banerjee, 1986). It should be noted that the differences recorded in blood parameters between various sizes according to Paizada et al, (1983), are genetically determined, but Chaudhuri et al, (1986) suggested that the difference might be due to the higher metabolic rate, of the bigger fish compared to smaller ones.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, from results in this study, globins present in the haemolymph of A. trapezia do not seem to show a Bohr effect unlike Hbs found in teleost fish species (Souza & Bonilla-Rodiguez, 2007;Witeska, 2013). The saturation of oxygen appears independent of pH as a significant drop in pH is coupled with a significant increase in sO 2 % for animals exposed to air for 12 h. This is consistent with previous studies on Hb containing bivalves such as Barbatia reeveeana (Grinich & Terwilliger, 1980), Cardita floridana (Manwell, 1963) and Anadara broughtonii (Furuta & Kajita, 1983) for which no Bohr effect was observed.…”
Section: And the Sea Mussel (Mytilus Edulis) Another Study On The Insupporting
confidence: 82%
“…Circulating Hbs may also be found within erythrocytes (intracellular) or freely dissolved in fluid tissue such as blood or haemolymph (extracellular) (Ching Ming Chung & Ellerton, 1980). Extracellular Hbs are extremely diverse in subunit size and quaternary structure, however, they all share the same globin fold as intracellular Hbs (Negrisolo et al, 2001 (Grinich & Terwilliger, 1980). Other examples of structural variation include annelid species, such as Riftia pachyptila and Lumbricus terrestris, which possess Hbs consisting of 24 and 144 subunits respectively (Royer et al, 2000;Strand et al, 2004;Flores et al, 2005).…”
Section: Myoglobins and Haemoglobinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red cells of the clam Barbatia reeveana have hemoglobins with two-domain chains and others composed of singledomain chains (25,26). The cDNA-derived amino acid sequence of 308 residues of the two-domain globin (27,28) shows that two very similar domains (78% identical) are connected by two lysine residues (Fig.…”
mentioning
confidence: 99%